When Land and Building Acquisition Taxes Are Due Based on a Sales and Purchase Agreement - Pamungkas, Hamka Sesario; Purnawan, Amin; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze the principle of transfer of land rights in the sale and purchase of land rights as a basis for determining the time of BPHTB debt and analyzing the legal aspects regarding PPJB as a basis for determining the time of BPHTB debt. This study uses a statute approach. This type of research is normative research. The type and source of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive. Based on the study, it is concluded that, when viewed from the perspective of national land law based on customary law, the time of transfer of land rights from the seller to the buyer is more appropriately interpreted as the time when the AJB is made and signed before the PPAT because it reflects the principle of clear and cash, which then the time of transfer of rights becomes the time when the BPHTB tax is owed and is the object of BPHTB as referred to in the provisions of Article 44 paragraph (1) of the HKPD Law. However, when viewed from the aspect of national development, the implementation of norms when BPHTB is owed based on PPJB as regulated in Article 49 letter a of the HKPD Law and its transitional provisions in Article 18 paragraph (2) letter a of the PP KUPDRD aims to close legal loopholes in the efforts of regional governments to increase tax revenue sourced from BPHTB as one of the instruments of fiscal decentralization. According to the Constitutional Court decision Number 117/PUU-XXI/2023 dated September 12, 2024, PPJB can have legal consequences for the transfer of rights from the seller to the buyer as long as the buyer has paid the land price in full and the buyer has taken control of the object of the sale and purchase and is carried out in good faith.